Metabolic Improvement via Enhancing Thermogenic Fat-Mediated Non-shivering Thermogenesis: From Rodents to Humans - Pan, Ruping; Zhu, Xiaohua; Maretich, Pema; Chen, Yong (Frontiers in Endocrinology, 2020)
Brown and beige adipose tissues play a large role in non-shivering thermogenesis (NST) in mammals, and subsequently have been studied for decades as potential therapeutic targets to treat obesity and its related metabolic diseases. However, the mechanistic regulation of brown/beige adipose tissue induction and maintenance in humans is very limited due to the ethical reasons. In fact, metabolic signaling has primarily been investigated using rodent models. A better understanding of non-shivering thermogenesis in humans is thus vital and urgent in order to treat obesity by targeting human brown adipose tissue (BAT). In this review, we summarize the anatomical and physiological differences between rodent and human BAT as well as recent advancements in human studies targeting thermogenic adipocytes as a means to combat metabolic diseases. Furthermore, we also discuss novel relevant strategies of therapeutic interventions and future investigations in this field.